WOMEN’S EMPOWERMENT IN COMPUTING: PROMOTING LEADERSHIP THROUGH EDUCATIONAL ROBOTICS - Ribeiro, Maria Ivanilse Calderon; Tamada, Mariela Mizota; Rios, Marcel Leite (Seven Editora, 2026)
The underrepresentation of women in Science, Technology, Engineering, and Mathematics (STEM) and computer science is a sociological challenge that demands incentive strategies from basic education onwards. This article presents the extension project "Robotic Girls: Creative Learning to Attract Girls to Robotics at IFRO". The project arose from the observation that 57.1% of students in the Technical Course in Informatics Concurrent with High School (CTICEM) did not identify with the field of computing, citing as obstacles a lack of confidence in their own abilities, limited access to resources, and financial challenges. The methodology adopted is based on Creative Learning and Problem-Based Learning (PBL), using Educational Robotics (ER) as a tool to connect theory and practice. The activities involved the use of block programming (Scratch), Lego Mindstorms EV3 kits, as well as support via a Virtual Learning Environment (VLE) and YouTube tutorials. The results demonstrate that the initiative promoted a significant increase in engagement: the number of participants rose from a low initial participation to the formation of all-girls teams for the Brazilian Robotics Olympiad (OBR). Beyond technical performance in competitions, the project stimulated female leadership, transforming students into knowledge multipliers through community workshops and visits to public schools. It is concluded that the RE (Research and Education), supported by mentoring programs and a collaborative environment, is an effective means to overcome gender barriers, strengthen self-confidence, and promote the empowerment of women in technology. DOI: https://doi.org/10.56238/sevened2026.008-003